The Relationship between Availability Basic Sanitation with Toddlers Stunting Incidence - Nara Raihani; Laili Rahayuwati; Desy Indra Yani; Windy Rakhmawati; Witdiawati Witdiawati (Journal of Nursing Care, 2023)
Poor basic sanitation was one of the indirect causes of stunting. Stunting was one of the toddler health problems which characterized by the child's height not according to his age. This study aims to analyze the relationship between the availability of basic sanitation facilities with stunting in toddlers incidence. This research was a correlational quantitative research with a cross-sectional approach. The total population in this study was 465 people in Sukamulya Village, Rancaekek District, Bandung Regency. Samples were taken by purposive sampling technique so that the sample used was 96, with the criteria of parents with toddlers. The instrument used was the RKDU questionnaire instrument originating from primary research which consisted of demographic data, questions related to the availability of latrines, questions related to waste management and questions related to SPAL. Data were analyzed using the chi- square statistical test. The results of statistical tests show that there was no relationship between the availability of basic sanitation facilities and the incidence of stunting in toddlers in Sukamulya Village (p value= 0,366). There are 22 respondents who still have poor sanitation facilities and 31 toddlers who still suffer from stunting. This needs to be give special attention from nurse to provide counseling interventions for sanitation facilities and stunting treatment.